2009
DOI: 10.1186/1546-0096-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans and Osgood Schlatter disease in a family with Stickler syndrome

Abstract: We observed that the nature of the articular and physeal abnormalities was consistent with a localised manifestation of a more generalised epiphyseal dysplasia affecting the weight-bearing joints. In these two patients, OCD and OSS appeared to be the predominant pathologic musculoskeletal consequences of an underlying Stickler's syndrome. It is empirical to consider generalised epiphyseal dysplasia as a major underlying causation that might drastically affect the weight-bearing joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…Conversely, Bradley and Dandy [3] reported an incidence of 1.2% based on an analysis of OCD lesions seen on the femoral condyles during 5000 knee arthroscopies, and Marsden and Wiernik found an incidence of 4% in all knee radiographs reviewed from 18,405 radiographs of male patients in a military hospital. To our knowledge, no previous studies have formally assessed the incidence of OCD in relatives of patients who had previously been treated for OCD of the knee, although some reports have described case series of lesions among twins [5,9,15,17,19,21] and families with genetic syndromes [1,24]. In each of these reports, including ours, the incidence among family members was higher than expected based on the incidence of OCD in the general population, suggesting an underlying genetic component to disease development.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Conversely, Bradley and Dandy [3] reported an incidence of 1.2% based on an analysis of OCD lesions seen on the femoral condyles during 5000 knee arthroscopies, and Marsden and Wiernik found an incidence of 4% in all knee radiographs reviewed from 18,405 radiographs of male patients in a military hospital. To our knowledge, no previous studies have formally assessed the incidence of OCD in relatives of patients who had previously been treated for OCD of the knee, although some reports have described case series of lesions among twins [5,9,15,17,19,21] and families with genetic syndromes [1,24]. In each of these reports, including ours, the incidence among family members was higher than expected based on the incidence of OCD in the general population, suggesting an underlying genetic component to disease development.…”
Section: Discussioncontrasting
confidence: 43%
“…For example, researchers have identified a specific mutation in the type IX collagen gene that results in a form of multiple epiphyseal dysplasia with associated OCD lesions [8]. Al Kaissi et al [1] described a family with a subset of Stickler syndrome in which OCD lesions were a constant syndromic component. This was linked to mutations in type II and XI collagen and inherited in an autosomal-dominant pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Stickler patients are occasionally given an erroneous diagnosis of Perthes disease as the appearances in some patients are similar radiologically. It is also common for adolescent Stickler syndrome patients to receive a diagnosis of Osgood Schlatters disease 32 but as this is a clinical rather than a radiological diagnosis (and that it is common in adolescence generally to have anterior tibial pain) the true nature of this association remains to be clarified.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Osteochondritis of primary ossification center i.e., OsgoodSchlatter disease is a traction apophysitis occurred due to overuse injury in knees of adolescent athletes [10]. This study showed that Osgood-Schlatter disease affected older children up to 14 years old.…”
Section: Discussionmentioning
confidence: 93%